2016
DOI: 10.1242/jeb.147637
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic inhibition of gonadotropin-releasing hormone neurons in the cichlid fish,Astatotilapia burtoni

Abstract: Dopamine regulates reproduction in part by modulating neuronal activity within the hypothalamic-pituitary-gonadal (HPG) axis. Previous studies suggested numerous mechanisms by which dopamine exerts inhibitory control over the HPG axis, ultimately changing the levels of sex steroids that regulate reproductive behaviors. However, it is not known whether these mechanisms are conserved across vertebrate species. In particular, it is unknown whether mechanisms underlying dopaminergic control of reproduction are sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
(55 reference statements)
1
14
0
1
Order By: Relevance
“…Brain lesion experiment and immunohistochemical studies in the goldfish C. auratus have revealed the existence of dopaminergic preoptico-hypophyseal pathway (Kah, Dulka, Dubourg, Thibault, & Peter, 1987) and altering action of DA on GnRH (Chang & Peter, 1983). Indeed, close association between GnRH and DA neurons in the preoptic area (POA) was demonstrated in the zebra fish D. rerio (Abraham, Palevitch, Gothilf, & Zohar, 2009;Fontaine et al, 2015), and study by Bryant, Greenwood, Juntti, Byrne, and Fernald (2016) has demonstrated that DA inhibits GnRH neurons in the preoptic area in the cichlid fish Astatotilapia burtoni. Furthermore, the dopaminergic actions are mainly mediated through DA-D2 receptor in teleosts (Dufour, Sebert, Weltzien, Rousseau, & Pasqualini, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Brain lesion experiment and immunohistochemical studies in the goldfish C. auratus have revealed the existence of dopaminergic preoptico-hypophyseal pathway (Kah, Dulka, Dubourg, Thibault, & Peter, 1987) and altering action of DA on GnRH (Chang & Peter, 1983). Indeed, close association between GnRH and DA neurons in the preoptic area (POA) was demonstrated in the zebra fish D. rerio (Abraham, Palevitch, Gothilf, & Zohar, 2009;Fontaine et al, 2015), and study by Bryant, Greenwood, Juntti, Byrne, and Fernald (2016) has demonstrated that DA inhibits GnRH neurons in the preoptic area in the cichlid fish Astatotilapia burtoni. Furthermore, the dopaminergic actions are mainly mediated through DA-D2 receptor in teleosts (Dufour, Sebert, Weltzien, Rousseau, & Pasqualini, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In teleosts, prominent preoptic projections have been described rostrally towards the ventral telencephalon, as well as caudally to reach the hypophysis for regulation of gonadotropins release (Fontaine et al, 2015;Holmqvist & Ekström, 1995;Rink & Wullimann, 2004). This dopaminergic control of reproduction mediated by inhibition of gonadotropin-releasing hormone is a conserved mechanism in vertebrates (Bryant, Greenwood, Juntti, Byrne, & Fernald, 2016).…”
Section: Telencephalonmentioning
confidence: 99%
“…Although most of the studies have suggested that DA acts primarily within the pituitary either indirectly by suppressing GnRH-releasing axons or directly by inhibiting the pituitary gonadotropes, a hypothalamic site for dopaminergic GnRH inhibition in fish was also implicated (Yu, Rosenblum, & Peter, 1991;Yu & Peter, 1992;Levavi-Sivan, Ofir, & Yaron, 1995;Van Goor, Goldberg, & Chang, 1998;Vacher et al, 2002). Recently, Bryant et al (2016) have demonstrated that DA directly interacts with GnRH neurons within the hypothalamic compartment in the cichlid fish Astatotilapia burtoni. Indeed, previous study by Bhat and Ganesh (2017) has demonstrated the presence of tyrosine hydroxylase (a marker for DA) immunoreactive neurons or fibres in the preoptic area and the PPD region of the pituitary gland in G. affinis.…”
Section: Discussionmentioning
confidence: 99%